(3LGeY GdCRgGQ hdWGFa GdCNHGQs - (3GdBeOj GdbjUQj, QLH Hf CMeO, HYO (B1087 (3g`s ((3eMeO Hf jhSas)
(3ChdgG (B:s
(3MeOG def LYd MOGFb CaFOJfG efhQI HCfhGQ GdEjeGf (B...(3GdJeShG efj cJGHG eTJedG jMJhj TjFG ef BjGJ GdbQBf hSff GdQSd hMce Cgd GdYQaGf hMcGjGJ GdGhdjGA GdcQGe hCNHGQ GdeTGjN GdYXGe (B...s
(3BNQgG (B:s
... (3abGd eG GdPj jWaj fGQ Lgfe ? bGd Ydjg GdSdGe (B: (3GdUHQ UOb QShd Gddg hUOb MHjH GdEdg (B, (3bGd GdEeGe GdeSJZaQj hGddg eG SeYJ MOjKG CLeY GdeMGSf GdTQjaI hecGQe GdGNdGb ef gPG GdMOjK JeJs
(3HYOg ChQGb aj GdJaSjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\18s
(3gOjI GdYGQajf (B1\366s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs